Energy supplementation in goats under a silvopastoral system of tropical grasses and leucaena - Carvalho, Wanderson; Oliveira, Maria; Alves, Arnaud; Moura, Raniel; Moura, Rosianne (Revista Ciência Agronômica, 2016)
The effect was evaluated of energy supplementation with ground maize grain on the performance and behaviour of Anglo-Nubian goats under a silvopastoral system of leucena and tropical grasses. The experiment was carried out in an area of Leucaena (Leucaena leucocephala (Lam.) De Wit.) intercropped with a herbaceous layer having a predominance of tropical grasses (Tifton 85, Andropogon and Guinea). A completely randomised design with four treatments and five replications was adopted. Growing goats were used; the control group being fed only on pasture, and the other groups supplemented with ground maize at 0.5, 0.9 and 1.3% of live weight. Supplementation reduced grazing time and increased rumination and idle time; although the goats spent approximately 85% of the time grazing on grasses, indicating a preference for this forage. Energy supplementation increased the weight gain per animal per unit area. Under a silvopastoral system of leucaena and tropical grasses, goats prefer the grasses, however, grazing on the legume results in a protein intake that justifies additional energy input. The supplementation of goats under a silvopastoral system of tropical grasses and leucaena, with maize as an energy source at a rate of up to 1.3% of live weight, influences feeding behaviour, having a favourable effect on animal performance.